Subarctic tidal flats in areas of large tidal range, southern Baffin Island, eastern Canada - McCann, S.; Dale, J.; Hale, P. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1981)
Wide, boulder-strewn intertidal flats occur around the head of Frobisher Bay and along parts of the shoreline of Cumberland Sound, in southeast Baffin Island. The coastal environment is characterized by large tidal ranges, severe winter sea ice conditions, and a relative sea level history which involves rapid and then decreasing land emergence during the earlier part of the Holocene, succeeded by slight recent submergence. Summer field investigations were carried out at two sites, Koojesse Inlet on Frobisher Bay, where ice breakup conditions were also monitored, and Pangnirtung Fiord off Cumberland Sound. The results are summarized under three headings: physical and biological zonation across the tidal flats; tidal action and sea ice processes; and geological evolution of the tidal flats. Comparisons are made with similar settings described by others in Labrador and Ungava Bay. The sedimentary shores at both Baffin Island sites exhibit a distinct physical zonation, most evident in the concentration of boulders in the middle tidal flat zone at Koojesse Inlet and in the boulder barricade at the seaward margin of the Pangnirtung flats. Biological observations show a zonation of intertidal flora and fauna across the intertidal zone at Koojesse Inlet. An outstanding problem concerns the mode of transport of very large boulders. Pushing and rolling, by ice floes which are confined to the intertidal zone by the solid ice in the offshore zone during the critical early phase of breakup may be more appropriate processes than ice rafting.